Expanding genomics of mycorrhizal symbiosis - Kuo, Alan; Kohler, Annegret; Martin, Francis M.; Grigoriev, Igor V. (Frontiers in Microbiology, 2014)
The mycorrhizal symbiosis between soil fungi and plant roots is a ubiquitous mutualism that plays key roles in plant and soil health, and carbon and nutrient cycles. The symbiosis evolved repeatedly and independently as multiple morphological types (e.g. arbuscular [AM], ectomycorrhizal [ECM]) in multiple fungal clades (e.g. phyla Glomeromycota, Ascomycota, Basidiomycota). The accessibility and culturability of many mycorrhizal partners make them ideal models for symbiosis studies. Alongside molecular, physiological, and ecological investigations, sequencing led to the first 3 mycorrhizal fungal genomes, representing 3 fungal phyla and 2 mycorrhizal types. The genome of the ECM basidiomycete Laccaria bicolor showed that the mycorrhizal lifestyle can evolve through loss of plant-degrading enzymes (PDEs) and expansion of lineage-specific gene families, including short secreted protein (SSP) effectors and other symbiosis genes. The genome of the ECM ascomycete Tuber melanosporum showed that the ECM type can evolve without expansion of gene families in contrast to Laccaria, and thus a different set of symbiosis genes. The genome of the AM glomeromycete Rhizophagus irregularis showed that despite enormous phylogenetic distance and morphological difference from the other 2 fungi, the symbiosis can involve similar solutions as loss of PDEs and mycorrhiza-induced SSPs. The mycorrhizal community is building on these studies with 3 large-scale initiatives. The Mycorrhizal Genomics Initiative (MGI) is sequencing 35 genomes of multiple fungal clades and mycorrhizal types for phylogenomic and population analyses. 17 MGI species whose symbiosis is reconstitutable in vitro are targeted for comprehensive transcriptomics of mycorrhiza formation. MGI genomes are seeding a set of 50+ reference fungal genomes for annotating metatranscriptomes sampled from 7 diverse well-described soil sites. These 3 projects address fundamental questions about the nature and role of a vital mutualism.